Use of instant messaging to improve participation in rehabilitative prescribed exercises for sufferers of Acquired Brain Injury: a feasibility study - Osato, Claudia Caterina (University of the Witwatersrand, Johannesburg, 2023)
This paper considers the feasibility of implementing an instant messaging program to improve participation in rehabilitative prescribed exercises for individuals with Acquired Brain Injury. Due to the common sequalae of brain injuries, such as prospective memory, motivation deficits and executive functioning, individuals with Acquired Brain Injuries (ABI) often do not complete homework. This study aimed 1) to create an instant messaging reminder Program to improve participation in rehabilitative prescribed exercise homework for individuals with Acquired Brain Injuries and 2) to assess the feasibility thereof. Four therapists participants were included in the study (two Occupational Therapists, one Physiotherapist and one Speech Therapist). Thematic analysis was utilised to assess responses to the semi-structured interviews to ascertain the therapists’ perceptions of the feasibility of the proposed intervention. An ethnographic approach explored the researcher’s experiences in relation to the process of the research. Results of the study included indications that due to both contextual and other challenges the Program could not be assessed for feasibility, as well as institutional challenges to implementation. The researcher found that the implementation of the proposed program was not possible due to various obstacles, which include, lack of ability to access public hospital patients, concerns of therapists regarding the sustainability of the intervention as well as changes and challenges in relation to the potential patients and participants. The researcher concluded that the implementation of the specific Program was not possible to implement in the context of both private and public rehabilitation services in Johannesburg and hence feasibility could not be ascertained.
A research submitted in partial fulfilment of the requirements for the degree of Masters of Arts, Department of Psychology (MA Psychology by Coursework and Research Report), to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, in 2023.
Keywords: Acquired Brain Injury; Barriers to research; Instant messaging; Theerapeutic homework; UCTD; SDG-3: Good health and well-being